Status of seed spices research and development in India - SINGH, BALRAJ; SOLANKI, R K (The Indian Journal of Agricultural Sciences, 2015)
The present paper reviews the research and development status of seed spices in India in the last seven decades. Seed spices are one of the important group of spice crops being cultivated in the arid and semi-arid region of the country. These crops are attaining importance day by day due to its aromatic and medicinal values, the present era is reflecting high International demand of Indian seed spices. The research achievements till date have been very concise for developing, numerous high yielding disease resistant or tolerant varieties, efficient production and protection technologies have also been developed during the period. Since 1930, we have gone long way in understanding the basic problems of these crops. The area of research have been focused mainly on designing packages to harvest more, production of better quality and consumer safe produce is yet to come. The ongoing compilation is a brief information of the milestones that has been bagged by the country's scientific and developmental team to sustain these crops. The problems and challenges in the cultivation of seed spices are enormous and each has to be answered with the changing climatic scenario in the time to come. New problems are also coming up in many of the seed spice crops. Cumin and coriander being the pre-dominant seed spice of the group needs more of the attention. The ongoing paper reflects the synchronized events that have happened in the country for seed spices research and development and also mentioning the significant achievements made and technologies which have shown considerable impact in sustaining these high value low volume crops under the hands of seed spice growers.